Dental Anatomy - Helvacioğlu Kivanç, Bağdagül (IntechOpen, 2018)
The book "Dental Anatomy" is one of the most important and basic areas of dentistry. This book is a collection of nine chapters divided into five sections as follows: Chapter 1: "Permanent Maxillary and Mandibular Incisors" Chapter 2: "The Permanent Maxillary and Mandibular Premolar Teeth" Chapter 3: "Dental Anatomical Features and Caries: A Relationship to be Investigated" Chapter 4: "Anatomy Applied to Block Anaesthesia" Chapter 5: "Treatment Considerations for Missing Teeth" Chapter 6: "Anatomical and Functional Restoration of the Compromised Occlusion: From Theory to Materials" Chapter 7: "Evaluation of the Anatomy of the Lower First Premolar" Chapter 8: "A Comparative Study of the Validity and Reproducibility of Mesiodistal Tooth Size and Dental Arch with the iTero Intraoral Scanner and the Traditional Method" Chapter 9: "Identification of Lower Central Incisors" The book is aimed toward dentists and can also be well used in education and research.